Optimizing Logistics by Using Machine Learning Algorithms - Rakhmonova Maftuna Nabijan qizi; Saida Safibullaevna Beknazarova (Periodica Journal, 2022)
Machine learning algorithms and the models they’re based on excel at finding anomalies, patterns and predictive insights in large data sets. Many supply chain challenges are time, cost and resource constraint-based, making machine learning an ideal technology to solve them. Machine learning and AI-based techniques are the foundation of a broad spectrum of next-generation logistics and supply chain technologies now under development
Keywords: Logistics; Machine; Algorithms; development